البُعد التداولي في شعر الشاعرة سعيدة بنت خاطر الفارسي - حويـَّـر الشمس خالد; مكي فيصل الركابي ميعاد (Journal of College of Education, 2018)
The linguistics theory of pragmatic focused on the analysis of the discourse on its diversity, taking philosophical foundations to achieve communication between the speaker and the recipient by adopting the linguistic dimensions in the context, so many utterances came up with the hope of intentions of the text or discourse, most notably the verbal act of Austin and Searle, and who follows them and the explicit and implicit meaning and the cooperation principles by Grice. The West and the Arabs have adopted this new vision to analyze the text functionally, because the speaker takes into account some of the values ​​through which the comprehension is achieved with the recipient. The poetry may depend on some of the pragmaticutterances to achieve this purpose. The researcher has examined this thesis on a poetic text with linguistic elements including many intentionswhich distributed on some dimensions such as the human, spiritual, social, political, national and other aspects of the poetry of Omani SaidaBintKhater Al-Farsi, with academic achievement in the field of literary criticism. The research based on adoptions that determine its direction and its course - To see the problematic issues, and starting from them, such as the pragmatic relationshipwith poetry, and its relationship with intention, and the overlap of other sciences towards receiving. - To highlight the pragmatics values ​​in the poetry of Omanis, especially the Al-farsi poet. It is the significant goal of this research through selecting poetic verses, and analyzing them. - Clarify the pragmatics link with criticism , and prove its validity to be a critical approach or not. - Focusing on limited poems of the poet which published on the Internet after assuring their existence in her poem collections. - Beyond the axioms, towards the definition of pragmatics, and what it is related to as it has been known in the scientific arena. - Not to engage in all pragmatics procedures, but the researcher limited this research to study the speech acts on the basis of the items established by Austin, and what it has been added by Van Djik, and the cooperation principles in its four utterances , and the dictation dialogue, and taking into account the recipient, and to highlight the purpose of pragmatics through its two dimensions explicit and implicit.